2019
DOI: 10.1056/nejmoa1817364
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Particulate Air Pollution and Daily Mortality in 652 Cities

Abstract: The authors' full names, academic degrees, and affiliations are listed in the Appendix. Address reprint requests to Dr. Kan at P.O. Box 249, 130 Dong-An Road, Shanghai 200032, China, or at kanh@ fudan . edu . cn.Drs. Liu and R. Chen and Drs. Gasparrini and Kan contributed equally to this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
570
8
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 1,204 publications
(692 citation statements)
references
References 24 publications
37
570
8
17
Order By: Relevance
“…Such an increase in daily PM 2•5 concentration is estimated to induce an increase of at least 5•6% in daily all-cause mortality, 4•5% in cardiovascular mortality, and 6•1% in respiratory mortality, according to our global study from 2011, which included Sydney. 6 These estimates are close to a previous observation on the effects of bushfire events between 1997 and 2004, in Sydney. 7 In addition to its fatal effects, bushfire smoke has also been related to increased risks of hospitalisation and emergency department visits due to respiratory diseases such as asthma, chronic obstructive pulmonary disease, and respiratory infections.…”
Section: Bushfires In Australia: a Serious Health Emergency Under CLIsupporting
confidence: 87%
“…Such an increase in daily PM 2•5 concentration is estimated to induce an increase of at least 5•6% in daily all-cause mortality, 4•5% in cardiovascular mortality, and 6•1% in respiratory mortality, according to our global study from 2011, which included Sydney. 6 These estimates are close to a previous observation on the effects of bushfire events between 1997 and 2004, in Sydney. 7 In addition to its fatal effects, bushfire smoke has also been related to increased risks of hospitalisation and emergency department visits due to respiratory diseases such as asthma, chronic obstructive pulmonary disease, and respiratory infections.…”
Section: Bushfires In Australia: a Serious Health Emergency Under CLIsupporting
confidence: 87%
“…In addition, as a highly reactive exogeneous oxidant, NO 2 can induce inflammation and enhance oxidative stress, generating reactive oxygen and nitrogen species, which may eventually deteriorate the cardiovascular and immune systems 37,38 . The impact of long-term exposure to PM 2.5 on excess morbidity and mortality has also been well-established [4][5]8 . An early unpublished report that explored the impacts of air pollution on mortality found that 1 μ g/m 3 PM 2.5 was associated with 8% increase in COVID-19 mortality rates in the USA 39 .…”
Section: Discussionmentioning
confidence: 98%
“…Environmental factors, such as urban air pollution, may play an important role in increasing susceptibility to severe outcomes of COVID-19. The impact of ambient air pollution on excess morbidity and mortality has been well-established over several decades [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Liang L et al analysed the association between dairy SO 2 , NO 2 , O 3 , CO, PM 10 and PM 2.5 and hospitalisations for acute exacerbation of COPD in Beijing from 2013 to 2017 and the results indicated that exposure-response association of NO 2 with COPD cases was linear, while the SO 2 , CO, PM 10 and PM 2.5 were nonlinear, no significance was found in O 3 with COPD incidence [43]. Liu C et al investigated the air pollution and daily mortality in 652 cities, the results demonstrated that exposure-response association of PM 2.5 with mortality was non-linear [26]. However, till now, the exposure-response of associations of air pollutants and some certain diseases are not well consistent.…”
Section: Discussionmentioning
confidence: 99%